The development of a monitoring instrument to measure the strength of health promoting systems. (13th November 2019) - Fransen, G; Wagemakers, A; Molleman, G
Abstract: Background: In the region of the Municipality Health Services Gelderland-South, each municipality has its own health broker. He or she advises the local policy makers, signals/pleads for addressing health problems, and facilitates effective approaches. By doing this health brokers try to strengthen the local health promoting system. To show the results of health brokers and to monitor changes of the local health promoting system, the MHS needs a monitoring instrument. The aim of this study was to develop this instrument and to test it in practice. Methods: Participatory action (qualitative) research is used to develop an online questionnaire. Structured group processes with the health brokers has led to the identification and definition of eight variables, reflecting the health promoting system: collaboration, support, integrated approach, visibility of results, health monitor data assessment, consistency, reach of the target population and sustainability. A literature study identified appropriate instruments. The online questionnaire is expanded to test the reliability, to evaluate the usability and to gain insight into the strength of the health promoting system in 16 municipalities. Results: The questionaire is based on validated questionaires like the Coordinated Action Checklist, and contains 28 items. Sumscores per variable ranged from 0 (weak) to 100 (strong). Health brokers and their partners (N = 147, 4-9 per municipality) filled out the questionnaire. Support and collaboration had the highest mean scores (70, 5 resp. 69, 8), and visibility of results and sustainability the lowest (61, 3 resp. 59, 4). Differences between municipalities were identified and can be used to know which variables can be improved. The test-retest reliability (mean r = 0, 713) and the Crohnbachs alphas (all > 0, 70) were reasonable good. Conclusions: The questionnaire can help to provide useful insights in the strengths and weaknesses of the local health promoting system. Key messages: Eight variables reflect the health promoting system: collaboration, support, integrated approach, visibility of results, health monitor data assessment, consistency, reach and sustainability. The questionnaire can help to provide useful insights in the strengths and weaknesses of the local health promoting system.